CometChip enables parallel analysis of multiple DNA repair activities [DNA repair 106 (2021) 103176–103202] - Jing Ge; Le P. Ngo; Simran Kaushal; Ian J. Tay; Elina Thadhani; Jennifer E. Kay; Patrizia Mazzucato; Danielle Chow; Jessica Fessler; David M. Weingeist; Robert W. Sobol; Leona D. Samson; et al. (DNA Repair, 2024)

Inter-fractional portability of deep learning models for lung target tracking on cine imaging acquired in MRI-guided radiotherapy - Jiayuan Peng; Hayley B. Stowe; Pamela P. Samson; Clifford G. Robinson; Cui Yang; Weigang Hu; Zhen Zhang; Taeho Kim; Geoffrey D. Hugo; Thomas R. Mazur; Bin Cai (Physical and Engineering Sciences in Medicine, 2024)

Ecological consequences of large herbivore exclusion in an A frican savanna: 12 years of data from the UHURU experiment - Jesse M. Alston; Courtney G. Reed; Leo M. Khasoha; Bianca R. P. Brown; Gilbert Busienei; Nathaniel Carlson; Tyler C. Coverdale; Megan Dudenhoeffer; Marissa A. Dyck; John Ekeno; Abdikadir A. Hassan; Rhianna Hohbein; et al. (Ecology, 2022)
Diverse communities of large mammalian herbivores (LMH), once widespread, are now rare. LMH exert strong direct and indirect effects on community structure and ecosystem functions, and measuring these effects is important for testing ecological theory and for understanding past, current, and future environmental change. This in turn requires long‐term experimental manipulations, owing to the slow and often nonlinear responses of populations and assemblages to LMH removal. Moreover, the effects of particular species or body‐size classes within diverse LMH guilds are difficult to pinpoint, and the magnitude and even direction of these effects often depends on environmental context. Since 2008, we have maintained the Ungulate Herbivory Under Rainfall Uncertainty (UHURU) experiment, a series of size‐selective LMH exclosures replicated across a rainfall/productivity gradient in a semiarid Kenyan savanna. The goals of the UHURU experiment are to measure the effects of removing successively smaller size classes of LMH (mimicking the process of size‐biased extirpation) and to establish how these effects are shaped by spatial and temporal variation in rainfall. The UHURU experiment comprises three LMH‐exclusion treatments and an unfenced control, applied to nine randomized blocks of contiguous 1‐ha plots ( n = 36). The fenced treatments are MEGA (exclusion of megaherbivores, elephant and giraffe), MESO (exclusion of herbivores ≥40 kg), and TOTAL (exclusion of herbivores ≥5 kg). Each block is replicated three times at three sites across the 20‐km rainfall gradient, which has fluctuated over the course of the experiment. The first 5 years of data were published previously ( Ecological Archives E095‐064) and have been used in numerous studies. Since that publication, we have (1) continued to collect data following the original protocols, (2) improved the taxonomic resolution and accuracy of plant and small‐mammal identifications, and (3) begun collecting several new data sets. Here, we present updated and extended raw data from the first 12 years of the UHURU experiment (2008–2019). Data include daily rainfall data throughout the experiment; annual surveys of understory plant communities; annual censuses of woody‐plant communities; annual measurements of individually tagged woody plants; monthly monitoring of flowering and fruiting phenology; every‐other‐month small‐mammal mark–recapture data; and quarterly large‐mammal dung surveys. There are no copyright restrictions; notification of when and how data are used is appreciated and users of UHURU data should cite this data paper when using the data.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

The assessment of the genotoxicity of e-waste leachates from e-waste dumpsites in Metro Manila, Philippines - Z. F. Alam; A. J. V. Riego; J. H. R. P. Samson; S. A. V. Valdez (International Journal of Environmental Science and Technology, 2019)

Towards a realistic simulation of boreal summer tropical rainfall climatology in state-of-the-art coupled models: role of the background snow-free land albedo - P. Terray; K. P. Sooraj; S. Masson; R. P. M. Krishna; G. Samson; A. G. Prajeesh (Climate Dynamics, 2018)

Penicillium subrubescens, a new species efficiently producing inulinase - S. Mansouri; J. Houbraken; R. A. Samson; J. C. Frisvad; M. Christensen; D. E. Tuthill; S. Koutaniemi; A. Hatakka; P. Lankinen (Antonie van Leeuwenhoek, 2013)

Do chimpanzees (Pan troglodytes schweinfurthii) exhibit sleep related behaviors that minimize exposure to parasitic arthropods? A preliminary report on the possible anti-vector function of chimpanzee sleeping platforms - David R. Samson; Michael P. Muehlenbein; Kevin D. Hunt (Primates, 2013)

Phenotypic variation of baobab (Adansonia digitata L.) fruit traits in Mali - S. De Smedt; K. Alaerts; A. M. Kouyaté; P. Van Damme; G. Potters; R. Samson (Agroforestry Systems, 2011)

Decreased expression of Intestinal I- and L-FABP levels in rare human genetic lipid malabsorption syndromes - S. Guilmeau; I. Niot; J. P. Laigneau; H. Devaud; V. Petit; N. Brousse; R. Bouvier; L. Ferkdadji; C. Besmond; L. P. Aggerbeck; A. Bado; M. E. Samson-Bouma (Histochemistry and Cell Biology, 2007)

Nucleotide sequence of the 5′-terminus of Newcastle disease virus and assembly of the complete genomic sequence: agreement with the “rule of six” - R. J. Phillips; A. C. R. Samson; P. T. Emmerson (Archives of Virology, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

The Newcastle disease virus V protein binds zinc - M. Steward; A. C. R. Samson; W. Errington; P. T. Emmerson (Archives of Virology, 1995)

Sequence analysis of temperature sensitive and ?neuraminidase-tolerant? mutants of Newcastle disease virus (strain Beaudette C) - J. Hughes; K. Yusoff; R. Hardy; H. McCartney; P. T. Emmerson; A. C. R. Samson (Archives of Virology, 1991)

Preliminary studies on the efficacy and establishment ofRoptrocerus xylophagorum [Hym.: Torymidae], a parasitoid ofIps grandicollis [Col.: Scolytidae], in Australia - P. R. Samson; J. Smibert (BioControl, 1986)

The biology ofRoptrocerus xylophagorum [Hym.: Torymidae], with a note on its taxonomic status - P. R. Samson (BioControl, 1984)